Efficacy of Probiotics to Reduce Nosocomial Infection and Feeding Intolerance in Hospitalized Low Birth Weight Babies - Haque, Md Mozammel; Afroza, Syeda; Mollah, Abid Hossain (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Background and objective: Neonatal sepsis is associated with increased mortality and morbidity of newborns. Moreover, inability to tolerate enteral feeding contributes to prolonged hospital stay and nosocomial sepsis. Probiotics confers health benefit to host by altering the gut environment. This study aimed at determining the efficacy of probiotics in reducing nosocomial sepsis and feeding intolerance in hospitalized low birth-weight infants. Methods: A quasi experimental clinical trial to compare between newborn infants getting probiotics along with breast milk (experimental group) with those getting breast milk only (non experimental group). Study was conducted from June to December 2013 with a total of 49 newborns, weighing 1000 to 2000gm. Results: In weight category 1000-1250 gm, 15.8% developed culture proven sepsis in probiotics/experimental group (n=9) and 10.5% in breast milk/non experimental group (n=10); p value was 0.655. Feeding intolerance was developed in 10.6% of the probiotics group and 31.5% of breast milk group, p value was not significant but the mortality was significantly lower among the probiotics group i.e., 5.3% in probiotics group Vs 42.1% in breast milk group (p 0.018). Between weight range of 1250-1500 gm, sepsis and feeding intolerance showed no significant differences (p value 0.305 & 0.305 respectively) but mortality differed significantly (0% probiotics group Vs 20% breast milk group; p 0.043). In weight range 1500-2000 gm, the result was not statistically significant for sepsis (p value 0.292), feeding intolerance (p value 0.292) and mortality (p value 0.292). Mortality was significantly lower in two weight categories (1000-1250 gm & 1250-1500 gm) and hence the overall result showed significant difference in the statistical analysis (p value 0.001).There were no differences either in nosocomial sepsis or feeding intolerance between the probiotics group and the breast milk group. Conclusion: Probiotics does not have any impact in reducing nosocomial infection and feeding intolerance but the use of probiotics seems to reduce mortality especially in the lower weight category. J Bangladesh Coll Phys Surg 2018; 36(2): 48-52